Forest advisors’ perceptions of non industrial private forest owners’ diverse motivations in forestry - Åsnes,Helene (Student thesis series INES, 2025)
The coupled climate and nature crisis requires rapid mitigation that does not compromise biodiversity. Forests have the potential to improve environmental objectives in synergies depending on management. To better understand the motivations behind forest management practices among non-industrial private forest (NIPF) owners in Sweden, this study conducted a cross-sectional comparative analysis with quantitative and qualitative elements. Structured interviews were carried out with two distinct groups of forest advisors, separated by belonging to either the traditional, production-orientated forestry dominated by even-aged forestry (EAF), or the alternative, more ecologically based forestry dominated by continuous-cover forestry (CCF). The informants shared their perceptions of prevailing motivations in forestry among associated forest owners, focused on economic gain, nature’s contribution to people – with emphasis on mitigation and biodiversity, ownership feelings, sense of place and social norms. To complement the findings with observed trends, a temporal GIS analysis was conducted on two forest management indicators, dead wood and mixed-forests distribution, due to their relevance for biodiversity. An overall increase in environmental awareness was reported across both target groups from observed and measured data. A shared key motivation in forestry was the desire to maintain personal connections to the forests, in turn preserving both social and natural values. However, a lack of large-scale efforts to improve environmental objectives was identified among EAF-associated forest owners. This tendency was considered in light of implicatory climate denialism as a potential underlying driving force that hinders action. Ultimately, this research highlights the complex mix of emotional, cultural, and economic motivations that shape forestry in Sweden, and the need for policies that support forest owners in aligning their values with climate and biodiversity goals.
Keywords: Physical Geography and Ecosystem analysis; Critical Physical Geography; Forestry; Mitigation; Biodiversity; Nature’s Contributions to People; Ecosystem Services